El régimen de libre competencia en Colombia (2014)
By referring to the literature for this Article sources, is the positive reality that many works of degree, monographs, writings, articles, and even treaties that exist in this regard. However, the Universidad La Gran Colombia, through international agreement concluded with universities in other countries, provides an opportunity for students to attend international seminars, in this period (2014) the advance at the University of Porto in International Law and in Vigo (Spain) on competition Law and the Community and Spanish, topical issue Industrial Property which is considered to academically do not have detailed knowledge of what does mean the right to free competition , for which it is intended to place the reader slightly on a conceptual framework of the origin of the subject and representative for some countries and Colombia and the meaning of the right to free competition, to the events of 2014 in our country regarding the ""Diapers Cartel"" and however it is a process that has been advanced only at a preliminary stage (initiation of the investigation and formulation of the statement of objections) by the Superintendence of Industry and Commerce, hardly could delve into the subject and establish lateness or our legislation has shortcomings that regard"